2008
DOI: 10.1093/rheumatology/ken302
|View full text |Cite
|
Sign up to set email alerts
|

Skin autofluorescence is increased in systemic lupus erythematosus but is not reflected by elevated plasma levels of advanced glycation endproducts

Abstract: Skin AGEs and levels of sRAGE and sVCAM-1 were elevated in SLE patients, whereas levels of CML and CEL were comparable with controls. As sRAGE even further increased during endothelial activation, it might be hypothesized that sRAGE acts as a decoy receptor. Why this proposed mechanism is insufficient to prevent increased AGE accumulation in the skin of SLE patients has to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
56
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 46 publications
6
56
1
Order By: Relevance
“…In this particular study, skin autofluorescence was closely correlated with collagen-linked fluorescence and with the specific AGEs, with correlation coefficients greater than 0.40. However, 2 subsequent studies did not show significant association between skin autofluorescence and plasma concentration of AGEs in patients with type 1 diabetic mellitus (n = 68) [20] or systemic lupus erythematosus (n = 9) [26]. These latter observations are in line with the overall results of our study.…”
Section: Discussionsupporting
confidence: 92%
“…In this particular study, skin autofluorescence was closely correlated with collagen-linked fluorescence and with the specific AGEs, with correlation coefficients greater than 0.40. However, 2 subsequent studies did not show significant association between skin autofluorescence and plasma concentration of AGEs in patients with type 1 diabetic mellitus (n = 68) [20] or systemic lupus erythematosus (n = 9) [26]. These latter observations are in line with the overall results of our study.…”
Section: Discussionsupporting
confidence: 92%
“…RAGE is upregulated in SLE in the acute phase of glomerular injury in lupus nephritis (39). The spliced extracellular domain of RAGE (soluble RAGE) accumulates in the blood of SLE patients, and RAGE expression correlated with SLE disease severity (40). In addition, we demonstrated here that RAGE has high affinity to major pathogenic molecules (e.g., C3a, DNA, HMGB1, AGEs, C3a/DNA complex, and HMGB1/DNA complex) found in SLE.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, when compared with quiescent SLE, the blood sRAGE levels were significantly increased during active disease in the Dutch study. [31] This difference might be attributed to the fact that the latter study only included 10 SLE patients (9 Caucasians and 1 Asian). Also, the usage of different medication regimes could have been an influential factor.…”
Section: Discussionmentioning
confidence: 98%
“…[29,30] To date, only two studies have investigated the serum sRAGE levels in SLE patients, and they reported conf licting results. [31,32] However, experimental animal models have provided encouraging results about the therapeutic role of sRAGE. [33,34] All of these investigations indicate that it could represent a future therapeutic target in chronic inflammatory diseases.…”
mentioning
confidence: 99%